OPTIMIZING THE MENTAL QUALITY OF STUDENTS' LEARNING: A HOLISTIC APPROACH AT MAHAD ALY NURUL JADID - Sairafi, Sairafi (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Islamic boarding schools are educational institutions that make a real contribution to society, with all their advantages and disadvantages. Each Islamic boarding school has a distinctive character, both in cultural, institutional and scientific excellence aspects. This research aims to investigate and optimize the mental quality of student learning at Mahad Aly Nurul Jadid through a holistic approach. This research methodology involves surveys, interviews, and observations to gain an in-depth understanding of the students' mental learning conditions. The research results show that a holistic approach that includes physical, mental, emotional and spiritual aspects can contribute significantly to improving the mental quality of students' learning. Efforts to optimize the mental quality of learning involve developing holistic mental development programs, improving facilities, and creating an environment that supports the psychological well-being of students. The implication of this research is that a holistic approach in developing the mental learning of santri at Mahad Aly can be the basis for creating a more balanced educational environment and supporting the optimal growth of santri in cognitive, emotional and spiritual aspects. It is hoped that this study can contribute to the development of mental learning development strategies in similar institutions and enrich the literature on holistic Islamic education.